2019
DOI: 10.3390/nu11030695
|View full text |Cite
|
Sign up to set email alerts
|

Amount, Preparation and Type of Formula Consumed and Its Association with Weight Gain in Infants Participating in the WIC Program in Hawaii and Puerto Rico

Abstract: The aim of this study was to assess the association between amount (below or above recommendations), preparation (liquid vs. powder), and type (regular vs. hydrolysate) of infant formula consumed and weight in infants participating in the Women, Infant and Children (WIC) Program in Hawaii (HI) and Puerto Rico (PR). This was a secondary analysis of 162 caregivers with healthy term 0–2-month-old infants. Socio-demographics, infant food frequency questionnaires, and weight and length were assessed at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
2
4
0
1
Order By: Relevance
“…Fully formula‐fed infants experiencing potential overfeeding in this study were found to be consuming 26 additional kilocalories per day compared to fully formula‐fed infants not experiencing potential overfeeding. Graulau et al (2019) found that 43.2% of WIC‐participating mother‐infant dyads in Hawaii and Puerto Rico who use formula consumed formula above recommendations, 31 which is similar to the estimate of 37.41% from this national sample of WIC participants. In contrast to the presently reported association between potential overfeeding and infant weight, the study in Hawaii and Puerto Rico did not identify an association between amount of formula consumed (below recommendation vs at recommendation or above recommendation) and either weight gain during the 4 months follow‐up or weight status at the follow‐up visit between 4 and 6 months of age 31 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Fully formula‐fed infants experiencing potential overfeeding in this study were found to be consuming 26 additional kilocalories per day compared to fully formula‐fed infants not experiencing potential overfeeding. Graulau et al (2019) found that 43.2% of WIC‐participating mother‐infant dyads in Hawaii and Puerto Rico who use formula consumed formula above recommendations, 31 which is similar to the estimate of 37.41% from this national sample of WIC participants. In contrast to the presently reported association between potential overfeeding and infant weight, the study in Hawaii and Puerto Rico did not identify an association between amount of formula consumed (below recommendation vs at recommendation or above recommendation) and either weight gain during the 4 months follow‐up or weight status at the follow‐up visit between 4 and 6 months of age 31 .…”
Section: Discussionsupporting
confidence: 63%
“…Graulau et al (2019) found that 43.2% of WIC‐participating mother‐infant dyads in Hawaii and Puerto Rico who use formula consumed formula above recommendations, 31 which is similar to the estimate of 37.41% from this national sample of WIC participants. In contrast to the presently reported association between potential overfeeding and infant weight, the study in Hawaii and Puerto Rico did not identify an association between amount of formula consumed (below recommendation vs at recommendation or above recommendation) and either weight gain during the 4 months follow‐up or weight status at the follow‐up visit between 4 and 6 months of age 31 . This difference between the two studies may be due to the small sample size in that study, a follow‐up that was too short to detect differences, the categorization of anthropometric outcomes or unmeasured confounding factors.…”
Section: Discussionsupporting
confidence: 63%
“…While previous research suggests that breastfeeding is associated with a decreased obesity risk compared to formula feeding [21], only a few studies have investigated the association between amount of formula consumed and obesity risk among exclusively formula fed children. A study focused on WIC-participating children who were fully formula fed in Hawaii and Puerto Rico found no association between amount of formula consumed at 0-2 months and weight gain four months later [22]. Another WIC-focused study found that number of feeds per day was positively associated with weight gain between 6 and 12 months among fully formula fed infants.…”
Section: Discussionmentioning
confidence: 99%
“…Susu formula yang terhidrolisis tampaknya lebih mudah diserap, dapat memberikan respon rasa kenyang yang berbeda, dan dapat mempengaruhi berat badan secara berbeda dibandingkan dengan susu formula biasa. Selain itu, konsumsi susu formula di atas pedoman yang direkomendasikan dan kesalahan dalam memberikan takaran susu formula bubuk juga dapat menyebabkan pertambahan berat badan dengan cepat (Graulau et al, 2019).…”
Section: Pendahuluanunclassified